2014
DOI: 10.3855/jidc.3879
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and virological response to antiretroviral drugs among HIV patients on first-line treatment in Dar-es-Salaam, Tanzania

Abstract: Introduction: In Tanzania, the follow-up on antiretroviral therapy (ART) response is based on clinical outcomes. We investigated virological response and ARV resistance mutations in relation to clinical response in ARV-treated patients. Methodology: A cross-sectional study of a cohort of 150 patients taking first-line ART in Dar-es-Salaam was conducted. Data were collected using standardized questionnaires and patients' blood samples. HIV viral load testing and genotyping was performed on all viremic samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A similar study performed in Dar-es-Salaam, Tanzania, reported 15% virological failure rates amongst patients who have been on ART for a median of 20 months. [ 38 ] Our study found that participants who had higher levels of education or held formal employment were more likely to experience virological failure; however, we acknowledge that the number of participants who had secondary school and tertiary education or formal employment was small (n = 13). Conversely, participants who had heard of drug resistance and those whose treatment regimen has been constant since initiation ART were significantly less likely to have virological failure.…”
Section: Discussionmentioning
confidence: 79%
“…A similar study performed in Dar-es-Salaam, Tanzania, reported 15% virological failure rates amongst patients who have been on ART for a median of 20 months. [ 38 ] Our study found that participants who had higher levels of education or held formal employment were more likely to experience virological failure; however, we acknowledge that the number of participants who had secondary school and tertiary education or formal employment was small (n = 13). Conversely, participants who had heard of drug resistance and those whose treatment regimen has been constant since initiation ART were significantly less likely to have virological failure.…”
Section: Discussionmentioning
confidence: 79%
“…3,7,25,27,33 -36 Minor PI DRMs were observed in 27 patients, similar to what has been observed in other Tanzanian settings. 37 Only one of the PI mutations (V82T/S) is known to be associated with reduced susceptibility to PIs (atazanavir, indinavir, lopinavir and tipranavir) and potentially could have impacted second-line therapy in this patient. To our knowledge, none of the patients had received any ART regimen prior to enrolment into the parent TOV3 study, suggesting that these PI mutations were transmitted rather than acquired.…”
Section: Discussionmentioning
confidence: 95%
“…24,28 To our knowledge, this is the first well-powered study addressing virological effectiveness and the emergence of HIV-DRM among patients on the current WHO-recommended ART regimen in Tanzania under programmatic conditions. Our findings provide further evidence from rural African settings that higher virological suppression rates can be achieved when HIV treatment and care programmes are continuous and effectively managed.…”
Section: Discussionmentioning
confidence: 99%